2020
DOI: 10.3390/biology9120471
|View full text |Cite
|
Sign up to set email alerts
|

Different Stages of Alveolar Bone Repair Process Are Compromised in the Type 2 Diabetes Condition: An Experimental Study in Rats

Abstract: The aim of this study was to analyze the stages of the alveolar bone repair in type 2 diabetic rats evaluating the mechanism of mineralization and bone remodeling processes after dental extraction. Forty-eight rats were divided into normoglycemic (NG) and type 2 diabetes (T2D) groups. The upper right incisor was extracted and after 3, 7, 14 and 42 days the animals were euthanized. The following analyses were performed: immunolabeling against antibodies TNFα, TGFβ, IL6, WNT, OCN and TRAP, collagen fibers matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Previous studies showed that OrthoGen ® has the potential to form new bone tissue due to its three-dimensional structure, acting as a scaffold, which is essential for osteoblastic cells, in addition to being biocompatible and low-cost [22,33]. Alcohol interfered negatively, delaying the repair process, which is in agreement with previous studies, pointing out that chronic alcohol consumption inhibits mechanisms responsible for cell proliferation, which act directly on bone formation and remodeling [34][35][36].…”
Section: Alcoholic)supporting
confidence: 87%
“…Previous studies showed that OrthoGen ® has the potential to form new bone tissue due to its three-dimensional structure, acting as a scaffold, which is essential for osteoblastic cells, in addition to being biocompatible and low-cost [22,33]. Alcohol interfered negatively, delaying the repair process, which is in agreement with previous studies, pointing out that chronic alcohol consumption inhibits mechanisms responsible for cell proliferation, which act directly on bone formation and remodeling [34][35][36].…”
Section: Alcoholic)supporting
confidence: 87%
“… 10 reported that the pathology that occurred in diabetic rats was similar to diabetes in humans. Pitol Palin L. et al 11 showed that diabetes stimulates the inflammatory process in the first stage of the alveolar repair process 7 days after tooth extraction, which leads to disruption of the mineralization process and collagen fiber organization and a decrease in fiber count. Xu L. et al 8 showed in their study with 14-day follow-up that vascular endothelial cell function, osteoblastic function and matrix mineralization were impaired due to the increased inflammatory response due to high glucose levels, resulting in delayed healing of tooth extraction sockets.…”
Section: Discussionmentioning
confidence: 99%
“…Bone regeneration occurs through remodeling commanded by basic multicellular units (BMU) via osteoblasts and osteoclasts to renew bone and mainten of bone quality in the repair process [ 51 ]. The immunolabeling analysis enables the observation of tissue responses by expressing of proteins related to the bone repair process [ 42 , 43 , 44 ]. Runx2 immunolabeling was moderate in Auto/PG, discrete in TCP/PG, and intense in HA/PG, signaling that the group with HA showed an increase in differentiation of pre-osteoblasts to osteoblasts in activity, representing younger cells from the beginning of bone formation compared to the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was performed with an optical microscope (LeicaR DMLB, Heerbrugg, St. Gallen, Switzerland) by scores means (ordinal qualitative analysis); when the scores were subjected to discrete labeling (+), moderate labeling (++), and intense labeling (+++), it was considered positive for diaminobenzidine (ThermoFisher Scientific, Waltham, MA, USA), taking care to hold negative controls to evaluate the specificity of the antibodies. These scores were established according to previous studies [ 42 , 43 , 44 ], where light labeling represented about 25% of the immunolabeling area in the blades, moderate labeling represented about 50%, and intense labeling represented about 75%.…”
Section: Methodsmentioning
confidence: 99%